The Governance of Common Property in the Pacific Region - Peter Larmour (ANU E Press, 2013)
Common property has often been regarded as an obstacle to development and best-or inevitably-replaced by private or state ownership. However, there are now many well-documented examples of successful management of open-access resources, and experiments in 'co-management' by users, owners, and government officials. The idea that the government should intervene to remedy the defects of common property, perhaps by registration, is now contested by a celebration of indigenous systems of self-management (Bromley 1989, Bromley and Cernea 1989). Government intervention may sometimes make things worse. Common property claims are also part of indigenous peoples' defence and reaffirmation of political sovereignty. The following chapters offer perspectives on common property from different academic disciplines, and from different islands and regions within and around the Pacific ocean. The disciplines include Geography, Economics, Anthropology, Law, History, and Political Science. The Pacific region includes settler societies like Australia, New Zealand and Canada, where indigenous systems were marginaUsed, and islands like Papua New Guinea and Fiji, where they were conserved, and even strengthened during and after colonial rule. The word 'governance' in the title recognises the political context of property rights, and refers to the idea that order, including systems of property, is the outcome of interactions between governments, markets and communities (Larmour 1996a, 1996b).